(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2017)
The suspension system is the main part of the vehicle, where the shock absorber is designed mechanically to handle shock impulse and dissipate kinetic energy. The basic study of hydro pneumatic suspension system is carried out for GINAF rally truck which has been as a part of this project to get a basic idea regarding the system and applicability in commercial vans. As spring is basic element of any suspension system, study and analysis of the spring is carried out. Optimization of the spring for the generalized suspension is done and checked in modal as well as structural analysis in ANSYS. And found that the newly designed spring is feasible for Conventional as well hydro pneumatic suspension system. Applicability of this newly designed hydro pneumatic suspension is checked for Indian commercial delivery vehicle and stresses are found way under the maximum failure limit. Feasibility of hydro pneumatic suspension system including all the requirements has been checked in this project against wear, bumping etc. Also Feasibility of the whole system has been checked for front as well as rear wheels differently and found suitable.